Lack of financial literacy exacerbates SMEs’ appalling state in Gweru city. - MABHANDA, WILSON (IJRDO - Journal of Business Management, 2015)
Unless policy makers are taken to task the spirit of SMEs in Zimbabwe shall remain dampened for the unforeseeable future. Studies conducted confirmed SME owners ignorant pertaining to further challenges experienced in the business due to lack of financial literacy. The purpose of this study was to explore the impact of financial illiteracy to SMEs in spite of various interventions to promote growth of SMEs. All the participants of this study were purposefully selected in line with qualitative research approach used in data analysis. The researcher employed a qualitative research approach where document analysis, focus group discussions, open-ended questionnaires and face to face interviews were used. The study revealed that several factors that include lack of financial education contributed further to poor management skills, poor budgeting skills, lack of business information, poor decision making and lack of non business behaviour. The study revealed a considerable low level of financial literacy among entrepreneurs and this has far reaching consequences to the management of their ventures. Such factors worsened the state of SMEs in Zimbabwe. The study therefore recommends that the government, stakeholders, banks, financial support institutions and individuals conduct financial literacy programmes to revive and strengthen the viability of SMEs.